2016
DOI: 10.1248/cpb.c16-00021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism by Which Magnesium Oxide Suppresses Tablet Hardness Reduction during Storage

Abstract: This study investigated how the inclusion of magnesium oxide (MgO) maintained tablet hardness during storage in an unpackaged state. Tablets were prepared with a range of MgO levels and stored at 40°C with 75% relative humidity for up to 14 d. The hardness of tablets prepared without MgO decreased over time. The amount of added MgO was positively associated with tablet hardness and mass from an early stage during storage. Investigation of the water sorption properties of the tablet components showed that carme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Additionally, the disintegration time of the moisture-absorbed magnesium oxide tablets in Hightoromeal was shorter than that of newly opened tablets in Hightoromeal. It has been reported that voids in magnesium oxide tablets are decreased when the tablets absorb moisture 19,20 . This was because, although Hightoromeal easily invades newly opened tablets, the invasion of thickener into moisture-absorbed tablets may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the disintegration time of the moisture-absorbed magnesium oxide tablets in Hightoromeal was shorter than that of newly opened tablets in Hightoromeal. It has been reported that voids in magnesium oxide tablets are decreased when the tablets absorb moisture 19,20 . This was because, although Hightoromeal easily invades newly opened tablets, the invasion of thickener into moisture-absorbed tablets may be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…2,4-8) Sakamoto et al reported that MgO dissolved by moisture absorption forms solid crosslinks with powder particles as one of the mechanisms. 3) Moreover, they suggested that a part of MgO binds to water (H 2 O) and carbon dioxide (CO 2 ) to generate a hydromagnesite [Mg 5 (CO 3 ) 4 (OH) 2 •4H 2 O], which is involved in the formation of solid crosslinks. 4) In another study, physical structure, such as the presence or absence of voids, was also considered a factor in prolonging disintegration time.…”
Section: Etcmentioning
confidence: 99%
“…1) In addition, there are some reports that the hardness and mass of MgO tablet formulations tend to increase when stored under humidified conditions and that disintegration of the MgO tablet formulations is prolonged by humidification. [2][3][4][5][6][7][8] Prolonged disintegration time of MgO tablet formulations affects patient's sense of taking. Furthermore, it is difficult for patients with insufficient swallowing ability to take the formulations.…”
Section: Introductionmentioning
confidence: 99%
“…We thought the values of the tested tablet properties mainly fluctuated according to the moisture content of the tablets. In other words, these values should be constant as long as the moisture content reaches a level of saturation after storage under humid conditions [16][17][18]. For example, Yamazaki et al [18] studied the storage stability of original brand name and generic famotidine tablets after storage under humid conditions (27 • C, 55% RH) for 8 weeks.…”
Section: Som Analysis To Characterize the Change Behaviors Of Tablet mentioning
confidence: 99%